The Analysis Of Consonant ‘D’ Sound In Pronouncing Galela Language - Patrick R Linggar; Aprianto G Wairo (REFORM : Jurnal Pendidikan, Sosial, dan Budaya, 2022)
The objectives of this research are (1) to analyze the sound of the language in this case ‘D’ Consonant in Galela Language (2) to describe the form of ‘D’ sound in phonetic transcription. This research is qualitative descriptive research. The data was carried out through interview with native language of Galela tribe from April to November 2021. Based on the result of ‘D’ sound in Galela language are divided into lamino alveolar and voiced ‘D’ consonant. The sound in this case ‘T’ closes with the ‘D’ sound